2022
DOI: 10.24036/ld.v16i1.115206
|View full text |Cite
|
Sign up to set email alerts
|

The Function of English Usage on Linguistic Landscape of Padang: A Case Study on Khatib Sulaiman Street

Abstract: This study deals with linguistic landscape found on Khatiib Sulaiman Street, Padang. The aim of the study is to identify the dominant language of the monolingual, bilingual and multilingual signs and to investigate the function of English displayed on the signs. Thus, this study uses mixed method,  quantitative and qualitative, since the data and the analysis of this study is in the form of pictures and text and the justification is proven by the percentage. By using multilingualism approach on a linguistic la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In addition to the domination of English in Nusa Dua and Labuhan Bajo LL, English is in the second place after Indonesian and the most frequently used foreign language apparent in the Indonesia LL research. Ramadhani (2018), Pamuji and Khristianto (2018), Harbon and Halimi (2019), Riani et al (2021), da Silva et al (2021, Khazanah et al (2021), andZahara andWijana (2022) reported the phenomenon. English is present in technology-related signs and has a prestigious status in da Silva's (2017) research.…”
Section: Positions Of Indonesian English and Arabic In The Ll Researc...mentioning
confidence: 86%
See 2 more Smart Citations
“…In addition to the domination of English in Nusa Dua and Labuhan Bajo LL, English is in the second place after Indonesian and the most frequently used foreign language apparent in the Indonesia LL research. Ramadhani (2018), Pamuji and Khristianto (2018), Harbon and Halimi (2019), Riani et al (2021), da Silva et al (2021, Khazanah et al (2021), andZahara andWijana (2022) reported the phenomenon. English is present in technology-related signs and has a prestigious status in da Silva's (2017) research.…”
Section: Positions Of Indonesian English and Arabic In The Ll Researc...mentioning
confidence: 86%
“…Indonesian dominates the use of language in the Indonesian LL research. When a quantitative analysis is conducted, Indonesian is almost always apparent as the most dominant language ( 88%) apparent in the LL studies by da Silva (2017), Fakhiroh and Rohmah (2018)), Ramadhani (2018), Pamuji and Khristianto (2018), Harbon and Halimi (2019), Purwanto and Filia (2020), Riani et al (2021), da Silva et al (2021, Sianipar (2021), Paramarta (2022), Yusuf et al (2022), and Zahara and Wijana (2022). This seems to translate the National Language Regulation Number 24 of 2009 and the Presidential Regulation Number 63 of 2019 that Indonesian is the official language.…”
Section: Positions Of Indonesian English and Arabic In The Ll Researc...mentioning
confidence: 93%
See 1 more Smart Citation
“…The country's constitution also requires that only Indonesian be taught in all Indonesian schools (Coleman, 2016). The finding relates to the study that Javanese (Khazanah et al, 2021) and Minangnese (Zahara & Wijana, 2022) are local or regional languages that do not receive much attention in sign. Astillero (2017) also discovered that, while taking into account the multilingual inhabitants of Irosin, the languages present in the classroom demonstrate how little space local languages have in formal education, particularly in secondary education.…”
Section: Monolingualmentioning
confidence: 91%
“…Studies on how English is utilized throughout the linguistic landscape have been done by several researchers. In 2022, Zahara and Wijana conduct a linguistic landscape study in Padang entitled "The Function of English Usage on Linguistic Landscape of Padang: A Case Study on Khatib Sulaiman Street" (Zahara & Wijana, 2022). It aims at revealing the language dominance of monolingual, bilingual, and multilingual signs and investigating the functions of English used on the signboards.…”
Section: Introductionmentioning
confidence: 99%